Sub critical water-methanol condition of rice bran oil for biodiesel production. Issue 2 (April 2020) - Prihandini, G; Elizabeth, L
Abstract: Biodiesel produced in conventional way by using catalyst make environment harmful. Subcritical water is a new method, green technology which can be employed to convert rice bran with water and methanol to fatty acid methyl ester (FAMEs) or biodiesel with adding CO2 and N2 gas as co-solvent. The aim of this study to investigates the influence of operation condition of biodiesel production from rice bran oil. Some solvents concentrated, range of temperature, pressurized gas and reaction time were applied in this research. Rice bran, water, and ethanol were put into subcritical water reactor in a certain ratio at 40bar to carried out the reaction under subcritical condition. The best condition 30/10 methanol-water (v/v), t = 7 h, T = 200 °C, CO2 as co-solvent was highest yield oil obtained 18% with oleic acid methyl ester as the major identified biodiesel.